Is it Possible to Derive the Dresdner Correction Formula Using a Finite Element Program? - Janknecht, Peter (Klinische Monatsblätter für Augenheilkunde, 2021)
Introduction The aim was to construct a model cornea by CAD and finite element software to find out how the intraocular pressure compares to the forces for applanation at the outside of the model cornea. These data were to be compared to the Dresdner correction formula. Thereby, it was possible to find out whether the model was plausible and to find hints as to why a correction for how the intraocular pressure depends on the corneal thickness is necessary at all.Methods Using the open-source software FreeCad and geometrical data for the cornea of the literature, an average cornea was constructed. On this average cornea, a finite element analysis was performed using the free software z88aurora. The intraocular pressure was measured by applanation of the outer cornea. The necessary forces were analysed.Results In this model, the intraocular pressure had to be corrected depending on the corneal thickness. The correction factor was kmean; finite elements = 19.17 – 0.0334*corneal thickness. The necessary correction did not exclusively depend on the relation between the endothelial area and the area of the outer cornea: for this relation alone the correction would have been karea-relation = 1.0361 – 0.0006*corneal thickness.Discussion The model correction formula was close to the Dresdner formula. The relation between endothelial area and the area of the outer cornea could only explain about half of the necessary correction.
Keywords: FreeCad; z88aurora; finite-element-analysis; cornea; Dresden correction formula